Peran Santri dalam Optimalisasi Hafalan Al-Qur’an melalui Metode Sab’iyyah Berdasarkan Tafsir Surah Al-Qiyamah Ayat 16–17 di Rumah Tahfidz Raudhatul Huffadz - Ismi Muharrami F. (Kartika: Jurnal Studi Keislaman, 2026)
The development of Qur’an memorization among santri often faces problems of inconsistency, haste in adding new memorization, and weak long-term retention. This condition indicates the need for a structured, gradual, and sustainable tahfidz method. This study aims to analyze the role of santri in optimizing Qur’an memorization through the implementation of the Sab’iyyah method at Rumah Tahfidz Raudhatul Huffadz and to examine its relevance to the message of QS. Al-Qiyamah verses 16–17. This research employed a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation, then analyzed descriptively. The findings show that the Sab’iyyah method, consisting of sabaq, sabqi, and manzil, helps santri develop a more organized memorization pattern, strengthen memory retention, improve discipline, and cultivate calmness in memorizing the Qur’an. The active role of santri is reflected in consistent daily muroja’ah, time management, and commitment to maintaining recitation quality. The implication of this study emphasizes that successful tahfidz is not determined solely by the method, but also by santri’s independence, patience, and sustained commitment to preserving their memorization.